Spiritual struggles and resting pulse rates: Does strong distress tolerance promote more effective coping?. (August 2016) - Krause, Neal; Ironson, Gail; Pargament, Kenneth I.
Abstract: Research indicates that spiritual struggles (i.e., tensions and strains associated with sacred issues) are associated with greater psychological distress and diminished levels of well-being. However, fewer studies have assessed the relationship between spiritual struggles and indicators of physical health. The purpose of the current study is to see whether spiritual struggles are associated with clinically higher levels of resting pulse rates. In addition, an effort is made to see if the effects of spiritual struggles on resting pulse rates are offset for individuals with a strong sense of distress tolerance. Data from a recent nationwide survey suggest that spiritual struggles are associated with higher resting pulse rates, but only among individuals who do not have a strong sense of distress tolerance. Highlights: People with greater spiritual struggles are less likely to have normal resting pulse rates. Distress tolerance offsets the negative effects of spiritual struggles on pulse rates. Support for the study findings is provided by data from a recent nationwide survey (N = 1732).